Analisis backswing dan release ketepatan shooting dalam olahraga petanque - Ardhiyanto, Sigit; Widiyatmoko, Fajar Ari; Zahraini, Dian Ayu (YLPK Mahardhika, 2021)
The purpose of this study was to determine the effectiveness of the Petanque throwing technique in UKM UPGRIS. The method used in this research uses quantitative research methods with a comparative approach and is assisted by the Kinovea software application version 0.9.3 which is used to measure. Kinovea is one of the software used to analyze motion, using this application we can play the captured video for analysis. The results of this study concluded that based on the analysis of several samples, the athlete's height and arm length affected the size of the backswing and release angles. There are differences in backswing and release angles based on the hypothesis test for the distance of 6 backswing 68-113, an average of 95.33 and 52-96 releases, an average of 66.83, a distance of 7 backswing 67-113, an average of 103.18 and a 52-89 release, average 75.27 average, 8 backswing distance 78-119, 106.27 average and 58-90 release, 77.90 average, and 9 backswing distance 78-140, average 111.45 and 60-91 release, average 79.81. There is no significant difference in the type of shooting, because a significant value <0.05, H0 is accepted. The conclusion of this study is that the taller the athlete's body and arm length, the smaller the backswing and release angle used and vice versa. There are differences in backswing and release angles at shooting distances of 6 meters, 7 meters, 8 meters and 9 meters. There is no difference in backswing and release angles to the accuracy of shooting carreau, reussi, and touche types.